2000
DOI: 10.1159/000022964
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in an Andean Population from Peru and Regional Migration Patterns of Amerindians in South America: Data from Y Chromosome and Mitochondrial DNA

Abstract: The genetic variability of a Quechua-speaking Andean population from Peru was examined on the basis of four Y chromosome markers and restriction sites that define the Amerindian mitochondrial DNA (mtDNA) haplogroups. Forty-nine out of 52 (90.4%) individuals had mtDNA which belonged to one of the four common Amerindian haplogroups, with 54% of the samples belonging to haplogroup B. Among 25 males, 12 had an Amerindian Y chromosome, which exists as four haplotypes defined on the basis of the DYS287, DYS199, DYS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 28 publications
6
38
2
3
Order By: Relevance
“…Control region mtDNA typing of 114 maternally unrelated individuals showed that haplotypes were assigned to the four Native Americans haplogroups A2, B2, C1, and D1. Preliminary results showed a higher frequency of haplogroup C1 among the Yekuana (61%) that resembles other Northern 6 Amazonian groups and a lower frequency of haplogroup B2 (5%), which is consistent with the broader genetic pattern in Amazonia as well as in South America (Easton et al 1996;Lee 2009;Rodriguez-Delfin et al 2001;Vona et al 2005). All four haplogroups were identified in the village of Sharamaña and in order to further examine the four haplogroups in the broader context of South American phylogenies, all twelve haplotypes from the village were selected for whole mtDNA genome analysis.…”
Section: Population Samplessupporting
confidence: 57%
“…Control region mtDNA typing of 114 maternally unrelated individuals showed that haplotypes were assigned to the four Native Americans haplogroups A2, B2, C1, and D1. Preliminary results showed a higher frequency of haplogroup C1 among the Yekuana (61%) that resembles other Northern 6 Amazonian groups and a lower frequency of haplogroup B2 (5%), which is consistent with the broader genetic pattern in Amazonia as well as in South America (Easton et al 1996;Lee 2009;Rodriguez-Delfin et al 2001;Vona et al 2005). All four haplogroups were identified in the village of Sharamaña and in order to further examine the four haplogroups in the broader context of South American phylogenies, all twelve haplotypes from the village were selected for whole mtDNA genome analysis.…”
Section: Population Samplessupporting
confidence: 57%
“…Thus, early characterizations of genetic patterns in South America tended to assume that a pattern of high between-population differentiation essentially described the entire continent. More recent characterizations hypothesize an east-west continental divide in genetic variation, with the west (i.e., Central and Southern Andean populations) being considerably more undifferentiated and homogenous than the east (i.e., Amazonian populations) (Fuselli et al, 2003;Lewis et al, 2005;Luiselli et al, 2000;Rodríguez-Delfin et al, 2001;TarazonaSantos et al, 2001). Fuselli et al (2003), following Tarazona- Santos et al (2001), suggested that this east-west regional divide was due to independent evolutionary dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…10.0% (7) 50.0% (35) 14.3% (10) 21.4% (15) 4.3% (3) Merriwether et al (1995), Rodriguez-Delfin et al (1999) Contemporary Central Andean (Ancash) 9.1% (3) 51.5% (17) 18.2% (6) 21.2% (7) 0% (0) Lewis et al (2004) Contemporary Central Andean (Aymara) 6.4% (11) 67.4% (116) 12.2% (21) 14.0% (24) 0% (0) Merriwether et al (1995) Contemporary Central Andean (Atacameñ os)…”
Section: Discussionmentioning
confidence: 99%